Resonance‐Enhanced Absorption in Hollow Nanoshell Spheres with Omnidirectional Detection and High Responsivity and Speed. Issue 34 (18th July 2018) - Lien, Der‐Hsien; Dong, Zhenghong; Retamal, Jose Ramon Duran; Wang, Hsin‐Ping; Wei, Tzu‐Chiao; Wang, Dan; He, Jr‐Hau; Cui, Yi
Abstract: Optical resonance formed inside a nanocavity resonator can trap light within the active region and hence enhance light absorption, effectively boosting device or material performance in applications of solar cells, photodetectors (PDs), and photocatalysts. Complementing conventional circular and spherical structures, a new type of multishelled spherical resonant strategy is presented. Due to the resonance‐enhanced absorption by multiple convex shells, ZnO nanoshell PDs show improved optoelectronic performance and omnidirectional detection of light at different incidence angles and polarization. In addition, the response and recovery speeds of these devices are improved (0.8 and 0.7 ms, respectively) up to three orders of magnitude faster than in previous reports because of the existence of junction barriers between the nanoshells. The general design principles behind these hollow ZnO nanoshells pave a new way to improve the performance of sophisticated nanophotonic devices. Abstract : Resonance‐enhanced absorption in hollow nanoshell spheres is demonstrated to show improved optoelectronic performance and omnidirectional detection of light at different incidence angles and polarization. Response and recovery speeds of these devices are improved up to three orders of magnitude faster than the film device. The design concept paves a new way to improve the performance of nanophotonic devices.